Implementing Nearpod-assisted Inquiry Based Learning on Students’ Critical Thingking Skills at Fluids Topic - Finurikha Fina Udiana; Joko Budi Poernomo; Edi Daenuri Anwar (Universitas Negeri Semarang, 2026)
Research on Implementing Nearpod-assisted Inquiry Based Learning on Students’ Critical Thingking Skills at Fluids Topic. This research was conducted at SMA Negeri 3 Demak using a quantitative approach and quasi-experimental design , namely pretest posttest control group design. Data analysis techniques used homogeneity test, normality test, n-gain test, t-test, and Likert scale test. There is a difference in students' critical thinking skills between the experimental and control classes using the Nearpod -assisted Inquiry Based Learning model . Data analysis shows that the increase in critical thinking skills in the experimental class is in the high category, while in the control class it is in the medium category. Student responses to the implementation of the Nearpod-assisted Inquiry Based Learning model are in the very positive category. This is indicated by the percentage of responses of 77% in the strongly agree category and 22% in the agree category.